1987
DOI: 10.1177/026565908700300308
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of recasting : review and theory

Abstract: Recasts have been shown to be successful in promoting the language development of normal children. A RECAST is a discourse adjustment through which basic semantic information is retained while syntactic structure is altered. Little research to date has addressed the power of recasts in advancing the development of specifically language-impaired children. The language-impaired child is believed to be delayed, but not deviant from the normal child, in acquiring language. For this reason, it is suggested that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In recent years, studies of the facilitative effects of child-directed speech have been increasingly regarded as a valuable resource which can inform teaching and therapy (e.g. Watkins & Pemberton, 1987;Weistuch & Brown, 1987). In a recent publication, Bliss has suggested that' Question usage by individuals working with preschool children is likely to enhance their modal usage', and that 'Modals can be introduced into preschool curricula by recastings and frequent use of questions in order to enhance their usage' (Bliss, 1988: 260).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, studies of the facilitative effects of child-directed speech have been increasingly regarded as a valuable resource which can inform teaching and therapy (e.g. Watkins & Pemberton, 1987;Weistuch & Brown, 1987). In a recent publication, Bliss has suggested that' Question usage by individuals working with preschool children is likely to enhance their modal usage', and that 'Modals can be introduced into preschool curricula by recastings and frequent use of questions in order to enhance their usage' (Bliss, 1988: 260).…”
Section: Resultsmentioning
confidence: 99%
“…This research has often described parents of communicatively impaired children as more directive and controlling and less semantically contingent than parents of normal language learning children (see Chapter 5, McTear & Conti-Ramsden, 1992 for a review). Thus "parentrse" therapy has con-ccntrated on making parents less directive and controlling and more semantically contingent (Cross, 1984;Watkins & Pemberton, 1987;Weistuch & Byers Brown, 1987).…”
Section: Child-directed Speech As Therapymentioning
confidence: 99%
“…Imitation or production training is the technique most commonly associated with didactic teaching and modelling is the technique most often associated with the interactive approach. The latter has been developed to include expansion or recasting of the child's preceding utterance (Watkins & Pemberton, 1987;Nelson, 1991). Some attention has been paid recently to focused stimulation, a technique which requires more concentrated exposure to particular linguistic forms (Fey, Cleave, Long & Hughes, 1993;Girolametto, Pearce & Weitzman, in press).…”
Section: Specific Intervention Techniquesmentioning
confidence: 99%